Antidepressant sertraline increases thioflavin-S and Congo red deposition in APPswe/PSEN1dE9 transgenic mice - Liao, Ming-Hsuan; Lin, Yen-Kuang; Gau, Fong-Ying; Tseng, Chun-Che; Wu, Da-Chih; Hsu, Chu-Yuan; Chung, Kuo-Hsuan; Li, Rung-Chi; Hu, Chaur-Jong; Then, Chee Kin; Shen, Shing-Chuan (Frontiers in Pharmacology, 2024)
Depression is strongly associated with Alzheimer disease (AD). Antidepressants are commonly used in patients before and after their diagnosis of AD. To date, the relationship between antidepressants and AD remains unclear. In our study, we administered sertraline or paroxetine to wild type (WT) and APPswe/PSEN1dE9 (APP/PSEN1) transgenic mouse models for up to 12 months. We quantified the drug concentrations using LC-MS/MS analysis and measured serum serotonin level using an ELISA assay. Additionally, we evaluated the amyloid burdens through thioflavin-S and Congo red stainings, and recognition memory using the novel object recognition test. Our findings revealed that mice treated with paroxetine exhibited a significantly higher level of weight gain compared to the control group and increased mortality in APP/PSEN1 mice. After 12 months of antidepressant treatment, the sertraline level was measured at 289.8 ng/g for cerebellum, while the paroxetine level was 792.9 ng/g for cerebellum. Sertraline significantly increased thioflavin-S and Congo red depositions, along with gliosis, in both isocortex and hippocampus of APP/PSEN1 mice compared to the control group. Both antidepressants also led to a decreased recognition index in APP/PSEN1 mice. These findings suggests a potential role of sertraline in AD pathogenesis, emphasising the need to reassess the use of these antidepressants in patients with AD.